PERTANGGUNGJAWABAN TINDAK PIDANA MEMBAWA SENJATA API TANPA IJIN DI WILAYAH HUKUM PENGADILAN NEGERI PONTIANAK (ANALISIS PUTUSAN PENGADILAN NEGERI PONTIANAK NOMOR: 379/PID.SUS/2023/PN.PTK) - Umam Ma'arif, Mirojul; Rahmat, Diding (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
Every Indonesian citizen who wants to own a firearm must meet the requirements stipulated in Article 1 Paragraph (1) of Emergency Law Number 12 of 1951 concerning Firearms. This law is an amendment to Law of the Republic of Indonesia Number 8 of 1948. An example of a criminal act without the right to carry and control a firearm and its ammunition is in Decision Number 379/Pid.Sus/2023/PN.Ptk. The formulation of the problem raised is how to regulate the responsibility of perpetrators of criminal acts of carrying firearms without a permit based on Indonesian criminal law and How is the responsibility of perpetrators of criminal acts of carrying firearms without a permit in the jurisdiction of the Pontianak District Court? The purpose of this study is to find out and understand and examine the regulation of the responsibility of perpetrators of criminal acts of carrying firearms without a permit based on Indonesian criminal law. To find out and understand and examine the responsibility of perpetrators of criminal acts of carrying firearms without a permit in the jurisdiction of the Pontianak District Court. This type of research is normative legal research with a normative system regarding the principles, norms, rules of laws and regulations, agreements. This research approach uses the statute approach method, case approach and conceptual approach. In Decision Number 379/Pid.Sus/2023/PN.Ptk, the judge sentenced the defendant to 10 (ten) months in prison based on legal and non-legal considerations. Legal considerations include the prosecutor's indictment, criminal charges, evidence, elements of the article of the Emergency Law of the Republic of Indonesia Number 12 of 1951 concerning Firearms and Explosives, not Article 1 paragraph (1) of the same Law, even though the article actually regulates carrying firearms without a permit. In terms of non-legal considerations, it can be seen from the background of the perpetrator, the condition of the perpetrator, the religion of the perpetrator, and the attitude of the perpetrator when undergoing the examination process in court.